Small Molecule Inhibitor C188-9 Synergistically Enhances the Demethylated Activity of Low-Dose 5-Aza-2′-Deoxycytidine Against Pancreatic Cancer - Kong, Rui; Sun, Guangming; Li, Xina; Wu, Linfeng; Li, Le; Li, Yilong; Wang, Fei; Xuan, Ping; Yang, Shifeng; Sun, Bei; Hu, Jisheng (Frontiers in Oncology, 2020)
Aberrant DNA methylation, especially hypermethylation of tumor suppressor genes, has been associated with many cancers' progression. 5-aza-2'-deoxycytidine (DAC) can reverse hypermethylation-induced gene silencing by via regulating DNA methyltransferases (DNMTs) activity and low-dose of DAC was proved to exert durable antitumor effects on solid tumor cells. Nevertheless, no clinical effect of DAC has been made when fighting against pancreatic cancer. Hence, it is necessary to raise a novel therapeutic strategy that further enhance the efficacy of DAC but not increase side effect, which impede the utilization of DAC. In the present study, we have discovered that C188-9, a novel STAT inhibitor, could improve the anti-tumor effects of low-dose DAC in vivo and in vitro. Further study demonstrated that such improvement was attributed to re-expression of RASSF1A, a well-known tumor suppressor gene. BSP assay showed that C188-9 combined with DAC treatment could significantly reverse the hypermethylation status of RASSF1A promoter, which indicated that C188-9 could enhance the demethylation efficacy of DAC. Then, our data demonstrated that DNMT1 was the underlying mechanism that C188-9 regulates the demethylation efficacy of DAC. Overall, these findings provide a novel therapeutic strategy combined low-dose DAC and C188-9 to improve therapeutic efficacy by inhibiting DNMT1-inducing promoter methylation.